ATRASYS – accident tracking system with messaging coordinate using GPS and GSM technology for UiTM Shah Alam / Nur Athirah Adrus - Adrus, Nur Athirah (2018)
Nowadays, UiTM Shah Alam’s people use their own transports when they go to work or class. That have the other people use a public transport such as a bus. All people become rushing and because of that, an accident occurs and makes the statistic of accident in UiTM Shah Alam increases. It can give more problem to the driver and also emergency team such as the time for call and wait the emergency team come to the location of accident is wasted and the victim’s condition also can be more severe. Furthermore, the emergency teams become hard to identify whether the accident is a minor accident or major accident and also people sent a fake call or information of the accident to the emergency teams is the other problem. The objectives of ATRASYS system is to design, develop and testing the system properly. This system can alert the emergency team when an accident occurs by sending a message via using Short Message System(SMS). This system used to detect an accident that involve car vehicle’s driver and the driver also can inform to the emergency team whether an accident is minor or major accident. This project consists hardware and software development. In the hardware development, an ATmega328 Arduino UNO is a microcontroller that used to control the system. A force pressure sensor is used to detect an accident for a car vehicle. The other hardware is Global Positioning System(GPS) and Global System for Mobile Communication(GSM) which is used as a wireless communication that can detect location and send the coordinate of the location via SMS. For the software development, an Arduino IDE software is used to code the system by using C++ language that program in Arduino UNO microcontroller to allow the function of hardware devices. Furthermore, this system has been testing all the sensors to make sure that it has no any problem when combine together. All the sensors were successful testing and combine together.